1992
DOI: 10.1523/jneurosci.12-10-04037.1992
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical afferents controlling the activity of serotonergic neurons in the dorsal raphe nucleus: microiontophoretic studies in the awake cat

Abstract: Serotonergic (5-HT) neurons of the brainstem dorsal raphe nucleus (DRN) have been implicated in a diversity of physiological and behavioral processes in vertebrates. However, despite extensive information about the intrinsic properties and the efferent projections of this neurochemical system, little information is available regarding the afferents that control its activity. This study investigated the neurotransmitters that regulate the activity of DRN-5-HT neurons under physiologically relevant conditions, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 36 publications
7
96
1
Order By: Relevance
“…These results are consistent with reports that GABA inhibits DRN neuronal activity (Gallager and Aghajanian, 1976;Levine and Jacobs, 1992) and mediates IPSPs in DRN serotonergic cells (Pan and Williams, 1989). Also, reduced DRN neuronal discharge during sleep is associated with increased GABA release, and this reduction is reversed by bicuculline (Levine and Jacobs, 1992;Nitz and Siegel, 1997;Gervasoni et al, 2000).…”
Section: Intra-raphe Gabaergic Mechanisms Regulate Scn 5-ht Releasesupporting
confidence: 90%
“…These results are consistent with reports that GABA inhibits DRN neuronal activity (Gallager and Aghajanian, 1976;Levine and Jacobs, 1992) and mediates IPSPs in DRN serotonergic cells (Pan and Williams, 1989). Also, reduced DRN neuronal discharge during sleep is associated with increased GABA release, and this reduction is reversed by bicuculline (Levine and Jacobs, 1992;Nitz and Siegel, 1997;Gervasoni et al, 2000).…”
Section: Intra-raphe Gabaergic Mechanisms Regulate Scn 5-ht Releasesupporting
confidence: 90%
“…These monoaminergic cells are active during waking, decrease activity during non-REM sleep, and become inactive during REM sleep (Heym et al, 1982;Fornal et al, 1985;Sakai, 1986;Reiner and McGeer, 1987;Yamuy et al, 1995Yamuy et al, , 1998Thakkar et al, 1998;Gervasoni et al, 2000). Evidence suggests that the quiescence of these cells during REM sleep is attributable to GABA-mediated inhibition (Levine and Jacobs, 1992;Wang et al, 1992;Siegel, 1996, 1997a,b;Gervasoni et al, 2000). Because both the MnPN and the vlPOA project to the DRN and LC (Zardetto-Smith and Johnson, 1995;Steininger et al, 2001;Lu et al, 2002) and they both contain populations of sleep-active GABAergic neurons, they may be a source of inhibition of monoaminergic systems at REM sleep onset.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize the enhanced AMPA response observed in 5-HT neurons lacking GLUA1 is mediated by receptors composed of the remaining subunits, which effectively substitute for GLUA1. During quiet wake and in animals under anesthesia, AMPA receptors on 5-HT neurons do not appear to be tonically activated (Levine and Jacobs, 1992). However, some evidence suggests that AMPA-mediated glutamatergic tone does drive 5-HT firing during the active dark phase (Tao and Auerbach, 2000).…”
Section: Mechanisms Underlying the Behavioral Phenotypementioning
confidence: 99%
“…The principal receptor for fast glutamate-mediated signal transmission is the AMPA receptor. In the raphe nuclei, it has been shown that activation of AMPA receptors on 5-HT neurons leads to increased firing in these neurons and increased 5-HT release (Gartside et al, 2007;Levine and Jacobs, 1992). Four subunits of the AMPA receptor, GLUA1-A4, contribute to the formation of different cell-typedependent heterotetrameric receptors (Dingledine et al, 1999).…”
Section: Introductionmentioning
confidence: 99%